On the Origins of Calculation Abilities - A. Ardila (Behavioural Neurology)
A historical review of calculation abilities is presented. Counting, starting with finger sequencing, has been observed in different ancient and contemporary cultures, whereas number representation and arithmetic abilities are found only during the last 5000–6000 years. The rationale for selecting a base of ten in most numerical systems and the clinical association between acalculia and finger agnosia are analyzed. Finger agnosia (as a restricted form of autotopagnosia), right–left discrimination disturbances, semantic aphasia, and acalculia are proposed to comprise a single neuropsychological syndrome associated with left angular gyrus damage. A classification of calculation disturbances resulting from brain damage is presented. It is emphasized that using historical/anthropological analysis, it becomes evident that acalculia, finger agnosia, and disorders in right–left discrimination (as in general, in the use of spatial concepts) must constitute a single clinical syndrome, resulting from the disruption of some common brain activity and the impairment of common cognitive mechanisms.